EFFECTS OF ELECTROMAGNETIC FIELD ON THE NITROGEN, PROTEIN AND CHLOROPHYLLCONTENT AND PEROXIDASE ENZYME ACTIVITY IN OIL PALM (ELAEIS GUINEENSIS JACQ.)LEAVES - Mahmood , Maziah; Bee , Ooi Bee; Mohamed, Mahmud Tengku Muda; Subramaniam, Sreeramanan (Emirates Journal of Food and Agriculture, 2017)
The effects of electromagnetic fields (EMF) from 275 kV high voltage transmission line on physiological, biochemical and antioxidant system changes in oil palm leaves were investigated under field conditions. Oil palm leaves were exposed to EMF from power lines at distances of 0, 8.8, 17.6, 26.4, 35.2, 44, 52.8 and 61.6 m away from the transmission lines for six months and seven years. The results showed that EMF exposure increased the content of chlorophyll a, b and the total chlorophyll in oil palm leaves planted nearer to the power lines (at 8.8 m) and decreased it with increasing distance from the lines. The protein banding profile of the oil palm exposed to electromagnetic field of different strength for seven years were insignificantly different. Oil palm exposed to the EMF for six months had three different protein banding patterns, which were different in the banding intensities of certain protein bands. The peroxidase enzyme activity (POX) of oil palm directly below the 275 kV power line was significantly (p?0.05) higher. However, decreasing EMF strength signifying that exposure on oil palm for duration of both seven years and six months resulted in a stress related response. The POX activity bands from the oil palm exposed to EMF for both seven years and six months respectively showed that more banding intensity and number of bands were found in those planted nearer to the power lines with higher electromagnetic strength exposure.